2018
DOI: 10.4066/biomedicalresearch.29-16-2144
|View full text |Cite
|
Sign up to set email alerts
|

Effect of rope skipping combining calcium pyruvate on fat metabolism of female college students

Abstract: Objective: To study the effect of rope skipping combining calcium pyruvate on the fat metabolism of female college students. Methods: 60 cases of female college students who are over 58 kg were selected and equally divided into three groups. Group A was given single rope skipping exercise; group B was given single oral calcium pyruvate treatment; and group C was given rope skipping combining oral calcium pyruvate treatment. Groups A and C were given routine rope skipping for 60 min per d. Groups B and C were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 7 publications
0
5
0
2
Order By: Relevance
“…In terms of cardiovascular disease, most studies showed that Ca supplements or dairy product intakes were negatively related to blood lipids [ 47 48 49 50 51 52 53 54 ] ( Table 5 ). However, Ca supplements used in some studies contained other nutrients, making it difficult to evaluate the effect of Ca itself on blood lipids or cardiovascular disease [ 47 51 52 53 ]. Several studies examined the effect of Ca on blood lipids by supplementation with Ca-rich supplements, not the dietary intake [ 41 47 52 53 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of cardiovascular disease, most studies showed that Ca supplements or dairy product intakes were negatively related to blood lipids [ 47 48 49 50 51 52 53 54 ] ( Table 5 ). However, Ca supplements used in some studies contained other nutrients, making it difficult to evaluate the effect of Ca itself on blood lipids or cardiovascular disease [ 47 51 52 53 ]. Several studies examined the effect of Ca on blood lipids by supplementation with Ca-rich supplements, not the dietary intake [ 41 47 52 53 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies examined the effect of Ca on blood lipids by supplementation with Ca-rich supplements, not the dietary intake [ 41 47 52 53 54 ]. In some RCT studies, there was no detailed information on the randomization process [ 51 55 ]. Several cross-sectional studies could not examine the causal relationship between Ca intake and outcomes [ 48 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…특히 피루빈산(pyruvate)은 유•무산소 에너지 대사의 중간 산물이자 우리 몸에서 자연스럽게 생성되는 물질로 서, 에너지 소비량 증가와 체중 및 체지방 감소 등에 효과 가 있다고 보고되었다 (Olek et al, 2014;Gong &Jiang, 2018). 유산소 운동으로 산소 공급이 지속될 경우에는 pyruvate는 젖산(lactate)으로 변환되지 않고, 미토콘드 리아로 이동하여 피르부산 탈수효소(pyruvate dehydrogenase: PDH)에 의해 아세틸 보조 효소 A(acetyl coenzyme A)로 전환된다 (Schell et al, 2014).…”
unclassified
“…과거부터 쥐 또는 인간을 대상으로 pyruvate 효과를 규명한 연구에서도 신체구성의 변화, RMR의 증가, 그 리고 혈중 지질 개선 등의 긍정적인 결과가 보고되었다 (Cortez et al, 1991;Gong & Jiang, 2018). Kalman et al(1999) (Morrison et al, 2000;Hermann et al, 2004), 주로 신체구성 및 혈중 지질 등의 변화를 확인하였다 (Onakpoya et al, 2014).…”
unclassified